Policy vs. Poverty: Evaluating Support Gaps and the Implementation of the Solo Parents Act Among Widows - Emil Arca (Future Science / FSH-PH Publications, 2026)
This study addresses the implementation gaps of the Expanded Solo Parents Welfare Act (Republic Act No. 11861) by evaluating how socio-economic status (SES) shapes the well-being of widows in the Fifth District of Bulacan, Philippines. Using descriptive statistics and semi-structured interviews with fifteen widows, the study explored socio-economic conditions, lived experiences, and support gaps. The findings reveal that widowhood leads to interconnected consequences, such as economic, health, psychological, and social threats. Outcomes varied according to dependency burden, pension and insurance coverage, and the availability of social assistance and support networks. Although Republic Act No. 11861 provides a formal framework for protection, most participants reported limited utilization of the available programs, indicating a disconnect between the legal provisions and community-level implementation. The study argues that widows’ well-being is shaped not only by material deprivation but also by their ability to translate formal entitlements into tangible support. By demonstrating how implementation gaps constrain access to existing protections, the study highlights the importance of strengthening policy implementation at the community level. The findings show that widowhood is shaped by both socio-economic disadvantage and institutional accessibility, positioning it as both a socio-economic and governance issue.